The lexical expressivity: between the expressive and the conative function of the language - Hradilova, Darina (Bohemica Olomucensia, 2013)
The following article returns to the topic, partly discussed in our older paper named K jednomu funkcnimu aspektu lexikalni expressivity (2012), and to its conclusions which pointed out the considerable shift of the lexical expressivity from the expressive to the conative function. The aim of this treatise is to analyse when it comes and which type of expressivity is applied to.